THE INFLUENCE OF ENTREPRENEURSHIP EDUCATION, ENTREPRENEURIAL MOTIVATION, FINANCIAL LITERACY, AND FAMILY ENVIRONMENT ON ENTREPRENEURSHIP INTEREST - Divayulia, Sastian; Wahjudi, Eko (Sekolah tinggi ilmu ekonomi pemuda, 2025)
This study aims to analyze the influence of entrepreneurship education, entrepreneurial motivation, financial literacy, and family environment on entrepreneurial interest among undergraduate students in Accounting Education at Surabaya State University. The background of this study is the low entrepreneurship ratio in Indonesia and the high unemployment rate among college graduates. The method used was quantitative with a causal approach. A sample of 70 students was selected using a purposive sampling technique. Data were collected through questionnaires and tests, then analyzed using multiple linear regression. The results indicate that entrepreneurship education, entrepreneurial motivation, and financial literacy have a positive and significant partial effect on entrepreneurial interest, while family environment has no significant effect. Simultaneously, all four variables significantly influence entrepreneurial interest. This finding emphasizes the importance of integrating education, motivation, and financial literacy in fostering students' entrepreneurial interest.